International investment positions and exchange rate dynamics: A dynamic panel analysis - Michael Binder; Christian J. Offermanns (Goethe University Frankfurt, Center for Financial Studies (CFS), 2007)
In this paper we revisit medium- to long-run exchange rate determination, focusing on the role of international investment positions. To do so, we develop a new econometric framework accounting for conditional long-run homogeneity in heterogeneous dynamic panel data models. In particular, in our model the long-run relationship between effective exchange rates and domestic as well as weighted foreign prices is a homogeneous function of a country's international investment position. We find rather strong support for purchasing power parity in environments of limited negative net foreign asset to GDP positions, but not outside such environments. We thus argue that the purchasing power parity hypothesis holds conditionally, but not unconditionally, and that international investment positions are an essential component to characterizing this conditionality. Finally, we adduce evidence that whether deterioration of a country's net foreign asset to GDP position leads to a depreciation of that country's effective exchange rate depends on its rate of inflation relative to the rate of inflation abroad as well as its exposure to global shocks.
urn:nbn:de:hebis:30-48547
Keywords: F31; F37; C23; 330; Exchange Rate Determination; International Financial Integration; Dynamic Panel Data Models; Wechselkurs; Volatilität; Kaufkraftparität; Internationale Kapitalmobilität; Standortfaktor; Schätzung; Welt